Developing video resources to reduce the burden of caring for persons with brain cancer. (October 2022) - Coyne, Elisabeth; Winter, Natalie; Carlini, Joan; Robertson, Julia; Dieperink, Karin
Abstract: Purpose: Co-designed and accessible video resources improve an understanding of health information and can reduce unmet needs for caregivers of persons with brain cancer. This study developed and evaluated video resources that provide health information for persons caring for someone with brain cancer. Method: A co-design approach with consumers was used to design, develop, and evaluate video resources. Results: Twelve videos were designed with persons with brain cancer, caregivers, and health professionals. The video design and topics were informed by current literature. The videos were filmed with consumers to ensure authenticity. The evaluation was completed using data analytics and seven interviews with consumers. Content analysis identified four themes: needing information, authenticity, visual engagement, and key messages. The video length and presentation were important aspects to engage the caregiver, particularly when dealing with stress. The storage on YouTube enabled accessibility and various presentation formats met different learning styles. Conclusion: The development of co-designed health information videos provided resources to improve caregivers understanding of the information provided by the health professionals. The videos were easy to access and able to be viewed at home with family. Highlights: Brain cancer diagnosis leads to complex challenges for the family to manage, such as personality changes and seizures. Family provides most of the care and support after cancer diagnosis, yet they often struggle with understanding information. Authentic video resources available via YouTube enable the person affected by cancer to access and understand information. Co-design enables resources developed with the consumer for the consumer and improves consumer outcomes.